The Effect of Using Picture Word Puzzle Games on Reading Skills Students SDN 13 West Bilah Labuhan Batu - Lili Kurniati; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to analyze the effect of using picture word puzzle games on the beginning reading skills of grade II students of SDN 13 Bilah Barat. The background of this study is based on the low beginning reading ability of students due to less varied and interesting learning methods. This study uses a quantitative approach with a One Group Pretest-Posttest Design, where the research subjects consisted of 22 grade II students. The research instruments were in the form of pretest and posttest tests, as well as observations during the learning process. The results of the data analysis showed that before the treatment, the average pretest score of students was 63.2, with only 36% of students achieving the Minimum Completion Criteria (KKM) of 70. After being given treatment using picture word puzzle games, the average posttest score increased to 81.4, with 86% of students achieving the KKM. Statistical analysis using the t-test showed that the t-count value (5.62) > t-table (2.08) at a significance level of 0.05, which means there was a significant difference before and after treatment. The results of this study indicate that picture word puzzle games have a positive and significant effect on students' early reading skills. With a more interactive approach, students become more motivated and active in learning. Therefore, the use of educational games such as picture word puzzles can be recommended as an alternative strategy in improving early reading skills in elementary schools